2003
DOI: 10.1080/15401420390271038
|View full text |Cite
|
Sign up to set email alerts
|

Problems Associated with the Recognition and Confirmation of Low-Dose Endocrine Toxicities

Abstract: Our attempts to confirm reports oflow-dose/hormetic effects in rodent endocrine toxicity studies are reviewed. It is concluded that our present failure to confirm any such effects is due, in large part, to a general lack of understanding of confounding influences and the failure of most investigators to confirm their findings before publication. The major potential confounding factor is suggested to be variability of the parameters under study within control groups, a factor that assumes increased importance w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Based to this result, it appears that BPA has some influence on the weight of ovary, without having significant effects on the body weight. This finding supports a previous report by Ashby et al [ 45 ]. In fact, any changes of 10% or greater in the organ weight is a strong indicator of toxic effects, particularly when it is associated with morphological changes.…”
Section: Discussionsupporting
confidence: 94%
“…Based to this result, it appears that BPA has some influence on the weight of ovary, without having significant effects on the body weight. This finding supports a previous report by Ashby et al [ 45 ]. In fact, any changes of 10% or greater in the organ weight is a strong indicator of toxic effects, particularly when it is associated with morphological changes.…”
Section: Discussionsupporting
confidence: 94%
“…However, these studies found no effect of low dose BPA and DES on prostate size and sexual maturation in both rats and mice [ 173 , 174 , 175 ]. The methodology employed by these early studies to look at low-dose effects of BPA has been highly scrutinized, potentially invalidating studies which found effects and those which did not [ 176 ]. Since then, the methodology used to measure BPA has been standardized by multiple researchers from different institutes.…”
Section: Bpa Regulatory Debatementioning
confidence: 99%
“…From work done in our laboratory during the collection of baseline histology data, we have rarely encountered NRGT animals (authors' unpublished data), which raises the question as to why control tank 1 had 5.5% NRGT animals. Ashby [29] asserts that low-dose endocrine toxicities are particularly difficult to detect because of the inherent variability within control groups of the parameters being studied. This variability within control animals may be influenced by a variety of factors, such as stress from overcrowding and naturally occurring endocrine-active compounds in food.…”
Section: Discussionmentioning
confidence: 99%